Five-year outcomes of transcatheter reduction of significant mitral regurgitation in high-surgical-risk patients. Issue 21 (4th August 2018) - Kar, Saibal; Feldman, Ted; Qasim, Atif; Trento, Alfredo; Kapadia, Samir; Pedersen, Wesley; Lim, D Scott; Kipperman, Robert; Smalling, Richard W; Bajwa, Tanvir; Hermann, Howard C; Hermiller, James B; et al.
Abstract : Objectives: This study evaluates the 5-year clinical outcomes of transcatheter mitral valve (MV) repair with the MitraClip device in patients at high risk for MV surgery treated in the Endovascular Valve Edge-to-Edge Repair (EVEREST) II High Risk Study (HRS). Methods: Patients with mitral regurgitation (MR) 3+ or 4+ and predicted surgical mortality risk ≥12% or surgeon assessment based on prespecified high-risk factors were enrolled. Patients prospectively consented to 5 years of follow-up. Results: At 5 years, clinical follow-up was achieved in 90% of 78 enrolled patients. The rate of postprocedural adverse events declined from 30 days to 1 year follow-up and was stable thereafter through 5 years. Two patients (2.6%) developed mitral stenosis (MS). Two patients underwent MV surgery, including one due to MS. A total of 42 deaths were reported through 5 years. Effectiveness measures at 5 years showed reductions in MR severity to ≤2+ in 75% of patients (p=0.0107), left ventricular (LV) end-diastolic volume (−38.2 mL; 95% CI −55.0 to –21.4; p<0.0001) and LV end-systolic volume (−14.6 mL; 95% CI −27.7 to −1.5; p=0.0303) compared with baseline. The New York Heart Association (NYHA) functional class improved from baseline to 5 years (p<0.005), and septal-lateral annular dimensions remained stable with no indication of mitral annular dilation through 5 years. Conclusions: The EVEREST II HRS demonstrated long-term safety and efficacy of MitraClip in high-surgical-risk patients through 5 years. The observed mortality was most likely a consequence of the advanced age and comorbidity profile of the enrolled patients, while improvements in NYHA class in surviving patients were durable through long-term follow-up. Trial registration number: NCT01940120 .